2013
DOI: 10.5056/jnm.2013.19.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Bloating: Pathophysiology and Treatment

Abstract: Abdominal bloating is a very common and troublesome symptom of all ages, but it has not been fully understood to date. Bloating is usually associated with functional gastrointestinal disorders or organic diseases, but it may also appear alone. The pathophysiology of bloating remains ambiguous, although some evidences support the potential mechanisms, including gut hypersensitivity, impaired gas handling, altered gut microbiota, and abnormal abdominal-phrenic reflexes. Owing to the insufficient understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 171 publications
0
71
0
1
Order By: Relevance
“…[4][5][6][7][8] Recently, a considerable number of studies have suggested that gut flora plays an important role in occurrence of symptoms and possibly the pathogenesis of FGID. [9][10][11] Bacterial flora in the proximal small intestine generally consists of aerobe and facultative anaerobic bacteria at ≤ 10 4 colony forming units (CFU)/mL in healthy subjects, while an abnormally high microbial population level in the small intestine is known as small intestinal bacterial overgrowth (SIBO). 12 Recent studies have suggested that SIBO may have a role in the pathogenesis of FGID.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Recently, a considerable number of studies have suggested that gut flora plays an important role in occurrence of symptoms and possibly the pathogenesis of FGID. [9][10][11] Bacterial flora in the proximal small intestine generally consists of aerobe and facultative anaerobic bacteria at ≤ 10 4 colony forming units (CFU)/mL in healthy subjects, while an abnormally high microbial population level in the small intestine is known as small intestinal bacterial overgrowth (SIBO). 12 Recent studies have suggested that SIBO may have a role in the pathogenesis of FGID.…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous symptoms in IBS may also arise from insufficient clearing of gases, or visceral hypersensitivity inducing symptoms even with normal levels of GI gas [11,12]. All these mechanisms are possible targets for medical treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Abdominal bloating in IBS may result from excess colonic fermentation with consequent gas production [9,10] or abnormal intestinal gas transit [11] and impaired tolerance of normal gas loads due to visceral hypersensitivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of PEA may, besides pain, include bloating and irregular bowel movements, though these are frequently associated with carbohydrate malabsorption syndromes. 2 We describe in a patient with PEA that the localized pain resolved within 3 weeks. Regression of inflammation including the reduction in size of the inflamed appendage in CT is demonstrated over the time period of 4 months.…”
Section: Introductionmentioning
confidence: 98%